Business basics for dentists - Willis, David O. (Ames, Iowa : Wiley-Blackwell, 2013)
Dr. David Willis combines his experience as a practicing dentist, educator, MBA, and certified financial planner in this breakthrough text about managing a dental business. Rather than a checklist of steps for success, Business Basics for Dentists describes business, economic, marketing, and management principles and explains how to apply them to the dental practice. Willis's aim is to help students and new practitioners understand how to use the core strategic and operational business philosophies to develop an effective dental practice. He provides the essential elements of a business.
Time Value of MoneyPresent Value of a Future Dollar; Capital Budgeting; Borrowing Money; Lease-purchase Decisions; 11 Business Taxes and Tax Planning; Principles of Business Taxation; The Basic Business Income Tax Formula; Employer Taxes; Unwithheld Expenses for the Employer; Miscellaneous Hiring Issues; Other Business Taxes; Business Tax Planning; 12 Management Principles; Characteristics of Dental Practice; Definition of Dental Practice Management; Functions of Dentist-Manager; Resources of the Practice; Roles of an Owner-Dentist; 13 Planning the Dental Practice; Practice Stages.
Includes index.
Print version record.
Keywords: Dentistry -- Practice; Dentistry -- Practice -- Finance; Dental offices -- Management; Practice Management, Dental; MEDICAL -- Surgery -- General; Dental offices -- Management; Dentistry -- Practice; Dentistry -- Practice -- Finance; Practice Management, Dental; Electronic books